Aset BUMN Sebagai Jaminan Atas Pinjaman Pemerintah Indonesia Kepada Lembaga Keuangan Asing - Kuras Purba; Sari Mandina; Andyna Susilawati (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This study discusses the State-Owned Enterprises (BUMN) as a legal entity established by the state to manage natural resources and strategic business branches not controlled by private individuals with the main goal of pursuing profits from state assets separated from the State Budget. As a legal entity, BUMN has assets because BUMN is a legal subject in both civil and criminal law, thereby having rights and obligations like any other natural person. The purpose of this research is to know the legal basis for regulating BUMN/State Assets and whether BUMN assets have legitimacy as collateral for foreign debt guarantees. This research uses a normative legal approach with a problem-solving approach using Conceptual approach, Statute approach, and Case approach. The legal materials used are the 1945 Indonesian Constitution, the Criminal Code, Law No. 16 of 2004 on BUMN, Law No. 1 of 2004 on State Treasury, and Law No. 17 of 2003 on State Finance."